2013
DOI: 10.5433/1679-0359.2013v34n3p1185
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do estresse inicial por baixo O2 combinado com 1-metilciclopropeno na conservação de maçãs ‘Royal Gala’ armazenadas com ultrabaixo O2

Abstract: ResumoO objetivo deste trabalho foi avaliar a realização de estresse inicial por baixo O 2 e sua interação com 1-metilciclopropeno (1-MCP) durante o armazenamento com pressões parciais ultrabaixas de O 2 (ULO) na conservação de maçãs 'Royal Gala'. O delineamento experimental utilizado foi o inteiramente casualizado, organizado em bifatorial. Os frutos foram submetidos a um estresse inicial por baixo O 2 por um período de 14 dias cada, com pressão parcial de 0,4 kPa de O 2 . Os tratamentos avaliados foram: Os f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
1
11
2
Order By: Relevance
“…However, the higher mealiness by fruit without 1-MCP not results in lower flesh firmness ( Figure 2D). This result disagree with some previously studies that found higher flesh firmness on fruit submitted to 1-MCP application (MOGGIA et al, 2010;BRACKMANN et al, 2013).…”
Section: Resultscontrasting
confidence: 56%
See 4 more Smart Citations
“…However, the higher mealiness by fruit without 1-MCP not results in lower flesh firmness ( Figure 2D). This result disagree with some previously studies that found higher flesh firmness on fruit submitted to 1-MCP application (MOGGIA et al, 2010;BRACKMANN et al, 2013).…”
Section: Resultscontrasting
confidence: 56%
“…The figure 1B shows that fruit submitted 1-MCP application have a lower and constant respiration rate throughout shelf life, according with BRACKMANN et al (2013). However, on fruit without 1-MCP application the respiration rate decreased up to the fourth day of shelf life.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations